2014
DOI: 10.1007/s13204-014-0372-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silver nanoparticles using medicinal Zizyphus xylopyrus bark extract

Abstract: In the present paper, biosynthesis of silver nanoparticles using Zizyphus xylopyrus bark extract is reported. Z. xylopyrus bark extract is efficiently used for the biosynthesis of silver nanoparticles. UV-Visible spectroscopy showed surface plasmon resonance peaks in the range 413-420 nm confirming the formation of silver nanoparticles. Different factors affecting the synthesis of silver nanoparticles like methodology for the preparation of extract, concentration of silver nitrate solution used for biosynthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(24 citation statements)
references
References 35 publications
(24 reference statements)
5
19
0
Order By: Relevance
“…The highest UV-visible peak is 445 nm at absorption 0.925 that confirms the for- mation of silver nanoparticles due to excitation of surface plasmon vibrations in silver nanoparticles. These results of color and UV-Vis spectrum agree with many recent studies for biosynthesis of AgNPs from plants and fungi extracts 9,20 .…”
Section: Characterization Of Silver Nanoparticlessupporting
confidence: 91%
See 1 more Smart Citation
“…The highest UV-visible peak is 445 nm at absorption 0.925 that confirms the for- mation of silver nanoparticles due to excitation of surface plasmon vibrations in silver nanoparticles. These results of color and UV-Vis spectrum agree with many recent studies for biosynthesis of AgNPs from plants and fungi extracts 9,20 .…”
Section: Characterization Of Silver Nanoparticlessupporting
confidence: 91%
“…and tested against some human pathogenic bacteria [8][9][10] . While Divband et al 11 used the produced nanoparticles from Z. spina christi fly ash to remove Lead (Pb…”
Section: Introductionmentioning
confidence: 99%
“…The pellet was washed thrice using deionised water to completely remove unwanted surface impurities from the nanoparticles. The pellets were dried on a Petri dish in a hot air oven at 60 C. [39,49] After drying completely, the powder was scraped off to yield silver oxide nanoparticles. These were stored in Eppendorf tubes at room temperature for further usage and analysis.…”
Section: Synthesis Of Silver Oxide Nanoparticles Using C Lanceolatusmentioning
confidence: 99%
“…Biosynthesized nanoparticles are more acceptable in medical applications due to more biocompatibility than chemically synthesized ones (Sundaram et al 2012). Previous reports suggested that the silver nanoparticles synthesized using medicinal plant extracts were capped by the organic components present in the plant extract (Maria et al 2014;Sasikala et al 2014). This will further enhance the therapeutic potential of these nanoparticles.…”
Section: Introductionmentioning
confidence: 99%